2018
DOI: 10.1371/journal.pgen.1007503
|View full text |Cite
|
Sign up to set email alerts
|

No unexpected CRISPR-Cas9 off-target activity revealed by trio sequencing of gene-edited mice

Abstract: CRISPR-Cas9 technologies have transformed genome-editing of experimental organisms and have immense therapeutic potential. Despite significant advances in our understanding of the CRISPR-Cas9 system, concerns remain over the potential for off-target effects. Recent studies have addressed these concerns using whole-genome sequencing (WGS) of gene-edited embryos or animals to search for de novo mutations (DNMs), which may represent candidate changes introduced by poor editing fidelity. Critically, these studies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 16 publications
12
52
0
Order By: Relevance
“…Our results are consistent with previous results in zebrafish demonstrating limited off-target activity at select predicted regions (Hruscha et al, 2013; Varshney et al, 2015) and with recent work in mice that found limited support for off-target effects genome-wide (Iyer et al, 2018). However, we are limited to detecting potential off-target variation within the exon-capture space of the genome.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous results in zebrafish demonstrating limited off-target activity at select predicted regions (Hruscha et al, 2013; Varshney et al, 2015) and with recent work in mice that found limited support for off-target effects genome-wide (Iyer et al, 2018). However, we are limited to detecting potential off-target variation within the exon-capture space of the genome.…”
Section: Discussionsupporting
confidence: 93%
“…However, the extensive characterisation of the target loci that ONT sequencing supports, in both founder and subsequent generations, does not suffice to validate newly mutated lines. Indeed, checks of off-target events (Anderson et al, 2018;Iyer et al, 2018), in particular, those physically linked to the locus of interest) and copy counting of the donor sequence by ddPCR to eliminate additional integrations remain essential and complementary steps to fully validate G1 animals (Supplemental Figures S3 and S4 and Codner et al, 2018).…”
Section: A Simple Processmentioning
confidence: 99%
“…Along those lines, the original study on WGS of CRISPR/Cas9 edited mice suggested the presence of extensive off-target mutations (14), which was, however, likely the result of an imperfect experimental design as pointed out in editorials (15)(16)(17)(18)(19). Further WGS investigations by Iyer and colleagues as well as our group (20,21) using trio studies demonstrated that CRISPR/Cas9 does not introduce an excess of off-target mutations. Therefore, it is prudent to examine critical issues of base editing, such as the extent of off-target mutations with a larger number of mice and under several conditions.…”
Section: Introductionmentioning
confidence: 95%